USAGE OF CARDIOPROTECTION PRINCIPLES IN TREATING CHRONIC HEART FAILURE - M. A. Gurevich; N. P. Sanina (Российский кардиологический журнал)
Usage of cardioprotection principles in treating chronic heart failure.